Cadaver study of anchorless implant for the treatment of anterior and apical vaginal wall prolapse. (March 2017) - Cervigni, Mauro; Ercoli, Alfredo; Levy, Gil
Abstract: Objective: This cadaver study was performed in order to evaluate the feasibility and the anatomical landmarks of a Self-Retaining device, a new unanchored mesh, for the treatment of anterior and apical vaginal prolapse. Study design: The Self-retaining device was implanted transvaginally in two cadavers. One cadaver underwent a detailed trans-abdominal dissection of the pelvis and the other cadaver, frozen after the implant placement, underwent a cross section dissection of the pelvis. Results: The location of the device was confirmed to be in appropriate anatomical position and in safe distance from any major neurovascular structures in the pelvis. Conclusion: The self-retaining implant, in its planned location, can be a safe procedure with respect to neighboring neurovascular and muscular pelvic structures. Brief summery: A cadaver study of anchorless implant for safety evaluation of the distance from vital structures. The implant found anatomically safe for use.